Islam di antara Modernisme dan Posmodernisme - Sutikno, Sutikno (Religió: Jurnal Studi Agama-agama, 2013)
Analyzing over modernism and postmodernism depict that both terms are conceived as a period or the phase of civilization that runs synchronically in one side and diachronic in other side. Synchronization from modernism to post-modernism constitutes the continuity of modernism as ongoing project. Meanwhile, diachronic approach is more describing that various critic and contestation toward modernity. In relation with this phase, the discourse of Islamic post-modernism has been rising before decades based on the complexity of cultural problems in the West, especially relating to the impact of modernity. Critics to modernity are not only because of social projects within culture but also of philosophical basis and root. Progress of mind achieved by Western society has eventually become a critic for modernity. Religion that is transforming from collective consciousness to private consciousness enhanced to be a new spirituality within the complexity of modernity. As an important part of global structure, Islam was also influenced by the impact of modernity. That is a logical consequence of dialectical process with Western culture, especially politics—such as system of democracy in the Muslim states. Religious fundamentalism is a response against Western modernity which is considered as in contradiction of Islamic values. This article focuses on critics to modernity, the rising of postmodernism, Islamic postmodernism and the essentials of postmodernism.